Cardiotoxicity of immunotherapy in lung cancer in light of new ESC guidelines - Gabriela B. Orzeł; Maciej Łydka; Justyna Lewandowska; Julia Stachowiak; Ewelina Szymańska; Katarzyna Mizia-Stec (Śląski Uniwersytet Medyczny w Katowicach, 2023)
There has been rapid development of anticancer therapies involving monoclonal antibodies targeting immune checkpoints of the immune response. One of them is pembrolizumab (the anti-programmed death receptor 1 ligand - anti-PD-1) used in the treatment of malignant melanoma, non-small cell lung cancer, or triple-negative breast cancer, among others. The case presented in this paper refers to a patient suffering from adenocarcinoma of the lung with multiple metastases and associated diseases. During immunotherapy with pembrolizumab, acute myocarditis was diagnosed. The clinical course of this case study specifically demonstrates how important, in the context of oncology patients treated with immunotherapy, the continuous evaluation and control are of the occurrence of adverse toxic effects associated with anticancer treatment. First of all, potential PD-1 inhibitor cardiotoxicity is rare in patients undergoing therapy with this drug, which significantly hinders accurate differential diagnosis in this direction. Second, this adverse effect, although relatively rare, is often fatal. The following case study describes how, with high doses of glucocorticosteroids, the effects of pembrolizumab-induced toxicity can be effectively muted.